Wide to multiband elliptical monopole reconfigurable antenna for multimode systems applications - I. H. Idris; M. R. Hamid; K. Kamardin; M. K. A. Rahim (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2019)
Wideband-multiband reconfigurable elliptical monopole antenna is investigated in this paper. By having conventional elliptical monopole antenna, wideband operating frequency is obtained. With the combination of dual pairs of slotted arms and a band-pass filter on the ground plane of the elliptical monopole, multiband is achieved. Dual-band operating frequencies at 1.6 GHz and 2.6 GHz while wideband operates from 3.35 GHz to 9 GHz. Therefore, wide range of wireless communication systems is obtained from the proposed antenna to support the multiband mode (i.e. GPS and LTE) and UWB systems. Frequency reconfigurable is achieved by controlling the switches integrated on the antenna structure. Simulated results of reflection coefficient, radiation patterns and gain performance are presented. The proposed antenna design is suitable candidate for different wireless communication applications.